Perancangan Alat Pengukur Suhu Tubuh Berbasis Mikrokontroler ATMega16 - Al Kautsar, Hanggoro Aji (LPPM Universitas Bina Sarana Informatika, 2021)
According to the World Health Organization (WHO) the transmission of corona disease is very fast spreading and quite deadly. One of the possible symptoms of Covid-19 is an abnormal body temperature above 380 C and below 360C. In this paper, the author wants to design an automatic body temperature measuring device based on infrared without touch to measure the measured human body temperature. Which is able to measure human body temperature with a distance of 15cm. The design of this body temperature measuring device uses the ATMega16 Microcontroller. Designed to make it easier to automatically detect body temperature without human assistance. For the temperature sensor we use the GY-906 MLX90614 sensor module, which is to measure temperature without touch with a maximum distance of 10cm and the laser module as a marker. To display the temperature, used 16x2 LCD and led lights as a marker. Then the author makes a distance setting if there are no objects at a distance of 10 cm on the temperature sensor, the sensor will automatically turn off with the HCSR-04 infrared module. The design of this tool is the best solution to solving problems in measuring body temperature in the current pandemic era. Automatic body temperature measurement is certainly better than manual body temperature measurement. And of course it will minimize contact which is one form of transmission of this virus.